2013
DOI: 10.1680/geng.11.00015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of offshore wind turbines supported on two foundations

Abstract: Offshore wind turbines are currently considered as a reliable source of renewable energy in the UK. These structures, owing to their slender nature, are dynamically sensitive at low frequencies, the first modal frequency of the system (less than 1 Hz) being very close to that of the excitation frequencies. The majority of operational offshore wind turbines situated in UK waters are founded on monopiles in water depths up to 30 m. For future development rounds where water depths are up to 70 m, alternative foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 13 publications
2
55
0
1
Order By: Relevance
“…Small scale 1-g tests reported by Lombardi (2010), Bhattacharya et al (2012), , Cox et al (2011) showed that the natural frequency of a wind turbine system changes with cycles of loading. The main reason for this change is the alteration of the foundation stiffness due to strain-hardening or strainsoftening behaviour of the soil supporting the foundation owing to the loading cycles.…”
Section: Dynamic Considerations In Design Of Wind Turbine Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small scale 1-g tests reported by Lombardi (2010), Bhattacharya et al (2012), , Cox et al (2011) showed that the natural frequency of a wind turbine system changes with cycles of loading. The main reason for this change is the alteration of the foundation stiffness due to strain-hardening or strainsoftening behaviour of the soil supporting the foundation owing to the loading cycles.…”
Section: Dynamic Considerations In Design Of Wind Turbine Foundationsmentioning
confidence: 99%
“…The testing apparatus and the methodology for monopile (Figure 4a) and tetrapod foundation (Figure 4b) can be found in Bhattacharya et al (2012). For the tetrapod structure, the model caissons were 7.4cm in diameter, 5.5cm deep and spaced at 40cm apart in two directions.…”
Section: Designing Experimentsmentioning
confidence: 99%
“…Three months after the installation the natural frequency dropped from its initial value of 1.28-1.32Hz to 1.13-1.15Hz. Scaled model tests carried out by Bhattacharya et al (2012Bhattacharya et al ( , 2013aBhattacharya et al ( , 2013b, Yu et al (2014), Guo et al (2015), Cox et al (2014) indicated that natural frequency may change owing to dynamic soil structure interaction.…”
Section: Introductionmentioning
confidence: 99%
“…To date a significant amount of research has been conducted into the serviceability of offshore foundations. The main focus of research has been into monopile foundations (LeBlanc et al, 2010a;Bhattacharya et al, 2012). More recently research has considered suction caissons focusing on scaled testing, modelling the monotonic caisson response (Feld, 2001;Houlsby et al, 2005;Villalobos, 2006), and the behaviour of a caisson subjected to a cyclic load (Byrne, 2000;Villalobos, 2006;Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%